A comprehensive assessment of genetic variation in serotonin transporter gene (5‐HTTLPR+rs25531) and the response to dapoxetine in Chinese patients with premature ejaculation. (12th June 2021) - Huang, Yuanyuan; Gao, Jingjing; Gao, Pan; Peng, Dangwei; Dai, Yutian; Jiang, Hui; Zhang, Xiansheng
Abstract: This study was to explore whether serotonin transporter gene‐linked polymorphic region polymorphisms (5‐HTTLPR+rs25531) influence the response to dapoxetine treatment in a Chinese population with premature ejaculation (PE). 112 patients with PE re‐enrolled from our previous study received dapoxetine monotherapy. At the endpoint, patients with S'S' had a significant increased risk of nonresponse compared with L' carriers ( p  < .001). The improvement in S'S' genotype was significantly lower in premature ejaculation profile (PEP) items of 'control over ejaculation' ( p  = .035) and 'distress related to ejaculation' ( p  = .017) than that in L' carriers. As to clinical global impression of change (CGIC), results in S'S' subjects showed significantly lower scores ( p  = .008) and a less satisfaction rate reporting at least 'better' ( p  = .020) compared with L' carriers. Moreover, our findings suggested that patients with S'S' were more likely to develop adverse effects (AEs) compared with L' carriers ( p  = .040). This study suggests that PE patients bearing the S'S' genotype have an inferior comprehensive efficacy and safety of dapoxetine treatment, which consist of poorer response in IELTs, less improvement in patient‐reported outcome (PRO) measures and greater incidence of AEs, than L' carriers. Variants of triallelic 5‐HTTLPR may play a major role as a predictor of treatment response to dapoxetine.